(untitled) (Al-Academy, 2016)
The present study aims at examining the stylistic development in the crafts of the sculptor Mohammed Ghani Hikmat. It gives answers to the following two questions: what is the nature of the stylistic development? And what are these principles and techniques led him to this development? The researcher has used the descriptive, analytic approach in examining the selected five samples out of the sculptor’s displayed crafts. The observational technique is used as a tool of examination. Among the main findings are: integrating space in the cubic crafts, represented by the existence of holes within this general construction of that space; the evident influence of critical contemporary orientations through the direct insertion of recipients in comprehending the ultimate crafts; a direct reference to Mesopotamia heritage ; the influence of the cultural environment on the stylistic realization; the humanitarian representation; and the expressive orientation as a stylistic procedure in performance